Consuming crisis : commodifying care and COVID-19 - Sobande, Francesca (London : SAGE Publications Ltd, 2023)
Consuming Crisis is a crucial account of how consumer culture capitalized on Coronavirus (COVID-19). Sobande explores how brands claim to care while they encourage people to'keep calm and consume'. This critical analysis of the power and politics of marketing examines an eclectic mix of campaigns, content, and experiences. Such work outlines the societal significance of fast-fashion adverts, banana bread's pandemic'moment', university social media strategies, and how digital technology mediates memories and work. Based on the belief that brands cannot be activists, Sobande creatively considers how brands construct care, camaraderie, culture, and so-called'normal' life during times of crisis. Francesca Sobande is a Senior Lecturer in Digital Media Studies at the University of Cardiff.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Covid-19 (Pandemic) -- Economic aspects; Organizational change; Covid-19 (Pandemic) -- Social aspects